Isolation and Characterization of the Flavonol Regulator CcMYB12 From the Globe Artichoke [Cynara cardunculus var. scolymus (L.) Fiori] - Blanco, Emanuela; Sabetta, Wilma; Danzi, Donatella; Negro, Donatella; Passeri, Valentina; Lisi, Antonino De; Paolocci, Francesco; Sonnante, Gabriella (Frontiers in Plant Science, 2018)
Flavonoids are a well-studied group of secondary metabolites, belonging to the phenylpropanoid pathway. Flavonoids are known to exhibit health promoting effects such as antioxidant capacities, anti-cancer and anti-inflammatory activity. Globe artichoke is an important source of bioactive phenolic compounds, including flavonoids. To study the regulation of their biosynthesis, a R2R3-MYB transcription factor, CcMYB12, was isolated from artichoke leaves. Phylogenetic analysis showed that this protein belongs to the MYB subgroup 7 (flavonol-specific MYB), which includes Arabidopsis AtMYB12, grapevine VvMYBF1, and tomato SlMYB12. CcMYB12 transcripts were detected specifically in artichoke immature inflorescence and young leaves and overlapped with the profiles of flavonol biosynthetic genes. Electrophoretic mobility shift assays (EMSAs) revealed that recombinant CcMYB12 protein is able to bind to ACII element, a DNA binding site ubiquitously present in the promoters of genes encoding flavonol biosynthetic enzymes. In transgenic Arabidopsis plants, the overexpression of CcMYB12 activated the expression of endogenous flavonol biosynthesis genes, leading to an increase of flavonol accumulation and a decrease of anthocyanins in leaves. Likewise, in transgenic tobacco petals and leaves, the overexpression of CcMYB12 decreased anthocyanin levels and increased flavonols.